Minimally helicity violating, maximally simple scalar amplitudes in N = 4 SYM - Bianchi, Marco S. (2012)
In planar N = 4 SYM we study a particular class of helicity preserving amplitudes. These are scalar amplitudes whose flavor configuration is chosen in such a way that only a limited number of diagrams is allowed, which exhibit an iterative structure. For such amplitudes we evaluate the tree level and one-loop contributions, providing a general formula valid for any number of particles. The ratio between the one-loop and tree level results is a simple combination of dual conformally invariant box functions with at most two massive legs. Along with the MHV and NMHV series, this constitutes the third known infinite sequence of one-loop amplitudes in N = 4 SYM.